Peran guru dalam meningkatkan minat baca peserta didik di bangku sekolah dasar - Yuliani, Diva Dwi (Maliki Interdisciplinary Journal, 2025)
Education is the main key in students self-development, and one important aspect that is often overlooked is reading culture. This indicates the need for emphais on reading culture, especially among students. It is important to teachreading skills and instill a love of reading from an early age, especially at the elementary school level. A high interest in reading contributes to the succs of the learning process, makes it easier for students to understand subject matter, and forms positive habits. Reading can also broaden students horizons and knowledge. Teachers must funtion as educators who not ony transfer knowledge but also act as motivators and facilitators to create a supportive learning environment. By prodiving acces to various interesting and elevant reading sources, as wall as holding enjoyable reading activities, it can foster a love of reading among students.